Breathing the Same Air? Measuring Air Pollution in Cities and Regions - Brezzi, Monica (OECD Regional Development Working Papers, 2014)
This paper presents a new set of estimates of exposure to air pollution (fine particulate matter - PM2.5) at the city, regional and national levels for the 34 OECD countries, and at the regional and national levels for Brazil, China, India, Russia and South Africa. The estimates are developed by the computation of satellite-based observations. They have the advantage of providing consistent values of the magnitude and spatial distribution of air pollution to be compared across and within countries and over time. The paper also explores the association between shape of cities (population density, share of built-up area, extension of the hinterlands, etc.) and air pollution. The estimates of air pollution at (TL2) regional level have been used in the newly released OECD Regional Well-Being Database as a measure of the environmental dimension